Analysis of Digital Marketing Strategies on the TikTok Platform for the Interlaken Perfume House Brand - Muhammad Ilham Fadhlurrahman; Onny Fitriana Sitorus (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study analyzes the digital marketing strategy of Interlaken Perfume House in enhancing consumer engagement and sales through social media. The research employed a descriptive qualitative approach with data collected through content observation, digital documentation, and in-depth interviews. The findings reveal that Interlaken utilizes TikTok as its main channel, implementing a content marketing strategy based on education, storytelling, and real-time interaction to build emotional closeness with consumers. SEO optimization, inbound marketing, paid advertising campaigns (PPC), call-to-action (CTA), and lead generation through social interaction are also applied, although not yet supported by an integrated data system. The success of the strategy is supported by creative content, message relevance to young audiences, and consistent engagement. The main challenges identified include limited resources, lack of customer data management, and inconsistent content production. This study recommends strengthening data-driven strategies through customer management systems to achieve long-term effectiveness.